Evolution of transition metal charge states in correlation with the structural and magnetic properties in disordered double perovskites Ca2−xLaxFeRuO6 (0.5 ≤ x ≤ 2). Issue 38 (22nd September 2021) - Naveen, Kumari; Rom, Tanmay; Islam, Shams Sohel; Reehuis, Manfred; Adler, Peter; Felser, Claudia; Hoser, Andreas; Nath, Ramesh Chandra; Yadav, Ashok Kumar; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Schmidt, Marcus; et al.
Abstract : La-based B-site disordered double perovskites, Ca2− x La x FeRuO6, have been investigated thoroughly. The effects of A-site substitution on the charge states and electronic and magnetic properties have been determined in a series of 3d/4d perovskites. Abstract : A series of disordered Ca1.5 La0.5 FeRuO6, CaLaFeRuO6 and La2 FeRuO6 double perovskites were prepared by the solid-state reaction method and investigated by neutron powder diffraction, X-ray absorption near-edge structure (XANES) analysis at the Ru–K edge, Mössbauer spectroscopy, DC magnetization and resistivity measurements. All compounds crystallize in the orthorhombic crystal structure with the space group Pbnm down to 3 K, showing a random distribution of Fe and Ru at the B site. Thermogravimetric analysis indicates oxygen deficiency in the Ca-rich and formal oxygen hyperstoichiometry in the La-rich members of the present series. While Mössbauer spectra verify the Fe 3+ state for all compositions, the XANES study reveals a variable Ru n + oxidation state which decreases with increasing La content. The end member actually is a Ru 3+ /Ru 4+ compound with possibly some cation vacancies. From magnetic susceptibility and neutron diffraction measurements, the presence of a G-type antiferromagnetic ordering was observed with a drastic increase in transition temperature from 275 K (Ca1.5 La0.5 FeRuO6 ) to 570 K (La2 FeRuO6 ). Mössbauer spectroscopy confirms the presence of long-range ordering but, due to local variations in the exchange interactions, the magnetic states are microscopically inhomogeneous. All the samples are variable range hopping semiconductors. A complex interplay between structural features, charge states, anion or cation defects, and atomic disorder determines the magnetic properties of the present disordered 3d/4d double perovskite series.